Principles of Islamic spirituality towards producing successful entrepreneurs: perspective of tariqah entrepreneur - Ahmad Fakhrurrazi Mohammed Zabidi; Abu Yazid Abdul Kadir; Salmy Edawaty Yaacob (Penerbit Universiti Kebangsaan Malaysia, 2023)
Islamic entrepreneurs are important to inculcate the principles of Islamic spirituality into themselves as well as their business. The life of a Muslim entrepreneur actually requires halal income, blessed profits, security in livelihood, and contribution to the poor. This article focuses on the principles of Islamic spirituality that can be practiced by an entrepreneur to succeed in their business. This article aims to discuss the key requirements in Islamic spirituality and practice for an entrepreneur. It will also discuss the basic relationship of Islamic spirituality with the 3 branches of knowledge (Fiqh, Tawhid, Sufism) for an entrepreneur. This study is a qualitative study that uses content analysis and interview methods for the findings of the study. The results of the study found that the basic principles of spirituality have existed in an entrepreneur whether Tariqah or not, entrepreneurial spiritual practices such as charity, prayer, and remembrance can actually build self -confidence and form a noble character. In addition, it suggests the need for future studies to find the differences between failed and successful entrepreneurs.